Treatment with cyclophosphamide, vindesine, cytarabine, dexamethasone and bleomycin in patients with relapsed/refractory diffuse large B-cell lymphoma. Issue 7 (July 2014) - Li, Minghui; Li, Yufu; Yin, Qingsong; Mi, Ruihua; Chen, Lin; Du, Jianwei; Wei, Xudong
Abstract Several chemotherapy regimens have been used as second-line therapies for relapsed and refractory diffuse large B-cell lymphoma (DLBCL). None have emerged as a preferred regimen. This retrospective study aimed to identify a regimen with high efficacy and low toxicity for patients with relapsed and refractory DLBCL. Fifty-eight patients diagnosed with relapsed or refractory DLBCL were included in the study. Patients were treated with cyclophosphamide, vindesine, cytarabine, dexamethasone and bleomycin (COAD-B). The overall response rate (ORR) was 70.7%, and the median remission duration was 13 months (3–48 months). The 1-, 2- and 4-year overall survival rates were 62.4%, 45.7% and 34.6%, respectively. The 1-, 2- and 4-year progression-free survival rates were 50.0%, 36.7% and 20.7%, respectively. The responses of patients with relapsed DLBCL to COAD-B were significantly better than those of patients with refractory DLBCL (p = 0.005). The main adverse reaction of patients was myelosuppression. Our data indicate that COAD-B should be used in treatment of patients with relapsed DLBCL.